The ritual of Kelvan - Mumbai Archive Project Team (Jio Institute, 2024)
Sakharpuda is followed by kelvan, another pre-wedding ritual where both families invite the bride and groom for a meal at their respective homes. This occasion also includes offering puja to their kuladevata (ancestral tutelary deity) to seek blessings.